PREVALENCE AND CORRELATING FACTORS OF ANXIETY AND DEPRESSION AMONG ALLIED HEALTH SCIENCES UNDERGRADUATES IN THE POST–COVID-19 ERA: A CROSS-SECTIONAL STUDY (Journal of Medical & Health Sciences Review, 2025)
Background:Undergraduate students are one of the most vulnerable groups around the globe and the COVID-19 pandemic has had a major effect on their mental health. It is possible to produce accurate post-pandemic mental health estimates for KMU students, a significant but understudied group in the area, by using such an AKUADS instrument for anxiety and depression within a multi-institute framework. In the wake of the COVID-19 pandemic, this study sought to determine the incidence of mental health distress among undergraduates enrolled in KMU Peshawar main campus institutes in Peshawar and to explore associated factors.Methods: Undergraduates participating in Khyber Medical University's allied health sciences programs were participants of this cross-sectional study. A validated AKUADS screening measure for depression and anxiety was utilized in the pre-structured questionnaire to collect the data. For the demographic data, SPSS version 24 was used to analyze the data using frequency and percentages; for associations, Pearson's chi-square test with statistical significance set at p